1D GEOMECHANICAL MODELING AND ITS IMPLICATION ON WELL PERFORMANCE IN NATURALLY FRACTURED RESERVOIR, MUARA LABOH GEOTHERMAL FIELD, WEST SUMATRA, INDONESIA - AL AMIN, TAUFIK
The effectiveness of geological structures to promote fluid flow is influenced by both geometric factors of the structural context and the local stress field. Multiple investigations have demonstrated that critically-stressed fractures/faults promote dilatation and slip in flow-friendly zones. One-dimensional (1D) geomechanics and critically-stressed fractures analyses are carried out in the five development well, ML-1, ML-2, ML-3, ML-4, and ML-5, in Muara Laboh Geothermal Field, West Sumatra, Indonesia. The main purpose of this study is to establish the permeability pattern on fractures/faults and its relationship to the present-day in situ stress. The analyses utilize wellbore data consisting of borehole images, gamma-ray (GR), shear and compressional sonic logs, pressure-temperature surveys, and drilling data. Geomechanical modeling applies empirical stress estimation to log data and pressure test results which is calibrated by stress polygon and the occurrence of wellbore failures. Linearized Mohr-Coulomb failure envelopes and failure criteria are used to determine the critically-stressed fractures. The 1D geomechanics model result shows that the in situ stress regime in all wells predominantly is strike-slip stress regimes with the maximum horizontal stress direction is about northeastsouthwest (NE-SW) following the far-field stress direction. Critically-stressed fractures are more likely to happen in the north northwest-south southeast (NNWSSE) direction and its reciprocal. The high intensity of critically-stressed fractures tends to be associated with productive interval/feed zones hence, it becomes the best well performance indicator.